A comparison between Caucasian and Asian superficial venous anatomy and reflux patterns – Implications for potential precision endovenous ablation therapy. (February 2020) - Lee, QWS; Gibson, K; Chan, SL; Rathnaweera, HP; Chong, TT; Tang, TY
Objectives: The aim of this study is to investigate whether there are differences between predominantly Caucasians and Asians from two disparate cohorts around the globe, with regard to their pre-operative venous reflux patterns and truncal vein characteristics, which could potentially help clinicians tailor venous treatment for chronic venous insufficiency on a more individualised basis in different parts of the world. Methods: A total of 200 lower limb chronic venous insufficiency duplex studies (127 Singaporean (predominantly Asian) patients) and 200 lower limb chronic venous insufficiency duplex scans (137 Americans predominantly Caucasians) were analysed and compared for differences in venous anatomy and reflux characteristics. Results: Asian patients from Singapore presented with higher CEAP scores compared to the predominantly Caucasian cohort from the US (30% CEAP 4a or greater vs. 17.5%; p < 0.01). Singaporeans had more great saphenous vein reflux starting at the sapheno-femoral junction (86% vs. 73%; p < 0.01) and ending at the ankle (93% vs. 46%; p < 0.01). Vein diameters were generally larger in the US cohort of patients (median 5.7 mm vs. 2.9 mm; p < 0.01). Conclusions: The predominantly Asian cohort from Singapore had smaller diameter truncal veins, longer segments of truncal vein reflux and present later with more advanced chronic venous insufficiency compared to their American counterparts. This information could help tailor endovenous ablation on a more individualised basis in the future.